2019
DOI: 10.3390/rs11141691
|View full text |Cite
|
Sign up to set email alerts
|

Hyplant-Derived Sun-Induced Fluorescence—A New Opportunity to Disentangle Complex Vegetation Signals from Diverse Vegetation Types

Abstract: Hyperspectral remote sensing (RS) provides unique possibilities to monitor peatland vegetation traits and their temporal dynamics at a fine spatial scale. Peatlands provide a vital contribution to ecosystem services by their massive carbon storage and wide heterogeneity. However, monitoring, understanding, and disentangling the diverse vegetation traits from a heterogeneous landscape using complex RS signal is challenging, due to its wide biodiversity and distinctive plant species composition. In this work, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
(137 reference statements)
1
21
0
Order By: Relevance
“…Causal relationships are not only limited to simple plant-environment interactions but also involve relationships among leaf, canopy, and soil parameters (Yue et al, 2020) or between vegetation indices and grain yield . Finally, objectives in the field of RS can also focus on assessing signal quality, evaluating, for instance, the variability of remote sensing signals related to plant communities (Bandopadhyay et al, 2019), seasons (Zarco-Tejada et al, 2016), or vegetation type .…”
Section: Goals In Remote Sensing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Causal relationships are not only limited to simple plant-environment interactions but also involve relationships among leaf, canopy, and soil parameters (Yue et al, 2020) or between vegetation indices and grain yield . Finally, objectives in the field of RS can also focus on assessing signal quality, evaluating, for instance, the variability of remote sensing signals related to plant communities (Bandopadhyay et al, 2019), seasons (Zarco-Tejada et al, 2016), or vegetation type .…”
Section: Goals In Remote Sensing Researchmentioning
confidence: 99%
“…Within the category of limitations related to research design, different studies have reported the following problems: a limited availability of plant biophysical data during the growth season (Molijn et al, 2018), a low number of variables included in the modeling of plant growth (Sofonia et al, 2019), a lack of specificity for detection methods that rely on phenotypic changes following decreases in chlorophyll concentrations and plant water potential, which can be caused by manifold stress types (Mahlein, 2016), uncertainties and error propagation associated with data processing due to a general lack of systematic analysis and calibration (Bandopadhyay et al, 2019), a lack of atmospheric data corrections, particularly for aerosol optical thickness and terrain altitude corrections (Davidson et al, 2006), the use of chemical and chlorophyll meter methods, which do not provide real-time measurements on a regional or global scale (Yu et al, 2014), the limited specificity of wavelengths related to crop/species that have been optimized for RRDIs, which cannot be extrapolated to other crops under different conditions (Yu et al, 2014), and the practice of attributing large changes in spectral shape to a given variable when data acquisition is temporally sparse (Magney et al, 2017).…”
Section: Errors and Limitationsmentioning
confidence: 99%
“…However, no significant SIF differences were observed due to water stress. In one of the recent HyPlant-related studies, Bandopadhyay et al [122] examined the sensitivity of SIF and vegetation indices from various heterogeneous ecosystems (i.e., grassland, forest, and peatland) and over peatland plant communities (i.e., Calamagrostietum neglectae, Sphagno recurvi-Eriophoretum angustifolii, Typhetum latifoliae, Cladietum marisci, etc.) using HyPlant data.…”
Section: Hyplant-related Sif Studiesmentioning
confidence: 99%
“…Stereovision and laser-scanning methods offer fascinating new opportunities for detecting and classifying plant architecture features such as branching angles, stem lengths, threedimensional leaf shapes and their distribution within canopies (Guo and Xu, 2016;Paulus et al, 2013;Wahabzada et al, 2015;Lottes et al, 2018). Such knowledge is crucially important for interpreting physiology-related vegetation signals such as sun-induced fluorescence from diverse vegetation types using airborne hyperspectral measurements and applying radiative transfer modeling (Bandopadhyay et al, 2019;Schickling et al, 2016). Using appropriate sensors, unmanned aerial systems (UAS) are increasingly used for carrying out such operations and determining phenotype characteristics (Roth et al, 2018).…”
Section: Remote Sensing Artificial Intelligence and Roboticsmentioning
confidence: 99%